You need to use the y = mx + b formula which will get you to the answer
y = -x -2
Step-by-step explanation:
(AUB)={1,2,3,4,6 }
(AUB)nC={1,2,3,4 }
OK the next step is to multiply 3r -1 by -7r
this gives us -21r^2 + 7r and we write it below -21r^2 + 25r
and subtract
This gives us 18r and we bring down the -6 to give
18r - 6
Finally we divide 18r by -3r to give -6 then add - 6 to the r^2 - 7r on the top
then multiply -3r - 1 by -6 to give 18r - 6
subtraction then leaves nothing.
so the answer is r^2 - 7r - 6